(untitled) (European Bison Conservation Newsletter, 2016)
Wisent Bison bonasus, as a priority species in the Natura 2000 requires particular interest and specialized treatment. A very important component of the protection of this endangered species is that people accept breeding activities and protective towards this species. Wisent in Bieszczady Mountains has already become a symbol of the region. However, for proper management of this species, there still is a lack of sufficient knowledge how it is perceived by the public. This paper was prepared on the basis of surveys, carried out in May 2016 in the Bieszczady Mountains. Assessed were the level of knowledge about the wisent, attitudes towards this species. Identified were also further actions allowing for better popularization of knowledge on nature conservation. Surveyed with questionnaires were three social groups of adult, permanent inhabitants of the Bieszczady Mountains, employees of State Forests, as well as young people from secondary schools and high schools. The study covered the communities of Baligród, Cisna, Czarna, Komańcza, Lesko, Olszanica, Lutowiska, Solina, Zagórz and Ustrzyki Dolne. Obtained results allow to conclude that an environmental education is very important part of life of the inhabitants of the Bieszczady Mountains. However, more attention should be paid to the creation and performance of the programs and educational workshops concerning the protection of nature. There is also a need for a concise book about wisent population inhabiting the Bieszczady Mountains reflecting the background of this species history and status in Europe.